CAPITAL INVESTMENT CRITERION FOR BULK ELECTRICITY TRANSMISSION INFRASTRUCTURE: A CONSUMPTION APPROACH - Smith, R.D.; Joubert, R.J.O. (The South African Journal of Industrial Engineering, 2011)
The primary technical function of an electric utility company is to supply electrical energy to its customers economically and at acceptable levels of reliability. The aspects of economics and reliability are however, competing constraints, since increased reliability of supply generally requires increased capital investment, which leads to higher prices for electricity. Traditional capital budgeting criteria, such as positive net present value, have been found to inhibit sound economic capital investment decision-making within the bulk electricity transmission environment. It is submitted that the results of this investigation will enable the operators of bulk electricity transmission systems to match the level of investment in reliability related infrastructure, with customers